'Immigrationization' of welfare politics? Anti-immigration and welfare attitudes in context. Issue 2 (23rd February 2021) - Burgoon, Brian; Rooduijn, Matthijs
Abstract: Several studies have shown that a person's attitude towards immigration affects his or her support for welfare redistribution. According to one view, negative attitudes towards immigration undermine support for welfare redistribution, as those who hold anti-immigration attitudes are thought to view immigrants as undeserving yet disproportionately drawing upon the welfare state. According to a competing view, however, anti-immigration attitudes awaken a person's own economic insecurities that in turn spur support for welfare protection and redistribution. This article argues and finds substantial evidence in European public opinion that both of these mechanisms can be at play and have implications that depend strongly on a country's national-level context. In particular, it is found that anti-immigration attitudes yield lower support for redistribution mainly when a respondent's country faces more immigration, when welfare-state protections are generous, and when migrants actually rely more than natives on the welfare state.